Characterization of ATP-binding cassette transporters associated with emamectin benzoate tolerance: from the model insect Drosophila melanogaster to the agricultural pest Spodoptera frugiperda. - Wang, L.; Guo, S.; Wen, B.; Deng, Z.; Ding, Q.; Li, X. (Pest Management Science, 2025)
Multiple families of detoxification genes, including the increasingly recognized family of ATP-binding cassette (ABC) transporters, work together to influence the toxicity of synthetic insecticides and thus their resistance. Effective management of insecticide resistance requires identification of all toxicity-affecting members from each family of toxicity-related genes. Here, we used emamectin benzoate (EB), ABC transporters and Spodoptera frugiperda as a working case to test whether the strategy of 'from the model insect Drosophila melanogaster to agricultural pests' can identify all or most ABC transporter members related to EB tolerance in S. frugiperda. After confirming the involvement of ABC transporters in the toxicity of EB against fruit fly with the ABC inhibitor verapamil, four ABC transporter genes (DmCG3327, DmCG11147, DmCG4822, and DmCG7627) were found to be involved in EB tolerance using RNA interference-based family-wide functional screening. A combination of phylogenic analysis and a reciprocal TBLASTN search identified five S. frugiperda ABC transporter members as homologs (SfABCC4, SfABCG1, and SfABCG23) or one-way best hits (SfABCG4 and SfABCG20) of the four fly ABC genes. Real-time quantitative polymerase chain reaction (qPCR) analysis found that all five S. frugiperda ABC transporter genes were inducible by EB, and expressed in all the developmental stages and larval tissues, but with significant quantitative differences among stages and tissues. A cytotoxicity assay of ABC-overexpressing Sf9 cell lines showed that all the five S. frugiperda ABC transporter genes made Sf9 cells tolerant to EB. This study not only identifies nine ABC transporter genes related to EB tolerance from D. melanogaster (four genes) and S. frugiperda (five genes), but also demonstrates the utility and effectiveness of the 'model to pests' strategy to identify most toxicity-affecting members from a given family of toxicity-related genes.